Phases of Construction and Difficulties of Developing Knowledge Tests in Educational Practice - Ivana М. Јeremić (Inovacije u Nastavi, 2023)
The paper presents the results of an empirical research which determined the stages of construction of knowledge tests in educational practice, the difficulties faced by teachers in the process of test development, as well as the ways of overcoming these difficulties. The descriptive-analytical research method, content analysis and survey techniques were used in the research. The research sample included 362 subject teachers employed in primary schools in Serbia. All respondents included in the research indicated the difficulties they face in the process of making tests, i.e., the ways of solving these difficulties. A sub-sample of a total of 80 teachers consisted of Serbian language and mathematics teachers who reported on the phases of the knowledge test construction in their practice. The results of the research indicate that teachers perceive only a small number of theoretically defined stages in the construction of knowledge tests. Certain differences were identified in explaining the phases among the teachers of Serbian language and teachers of mathematics. At the same time, two-thirds of the surveyed teachers face difficulties when they prepare knowledge tests independently. The existing difficulties are usually solved by consulting the more experienced colleagues or by searching for a solution independently. The author’s recommendation is to enable teachers by means of an additional teacher training courses, to acquire the appropriate knowledge and skills that would help them create the knowledge tests with satisfactory methodological characteristics, and at the same time adequate for the needs of their teaching practice.